Effects of composition ratio on structure and phase transition of ferroelectric nanocomposites from silicon dioxide nanoparticles and triglycine sulfate. (3rd June 2019) - Mai, Bich Dung; Nguyen, Hoai Thuong; Nguyen, Thi Kim Anh; Ta, Dinh Hien; Luu, Thi Nhan
ABSTRACT: The present work is devoted to study on influences of silicon dioxide nanoparticles (SiO2 ) on structure and phase transition of a classical ferroelectric of triglycine sulfate (TGS) by synthesizing a composite containing SiO2 and TGS at different composition weight ratios. Particle size analysis, X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) techniques were utilized to charaterize the synthesized composite. The experiments for investigation of phase transition were conducted from 20 to 120°C under a weak electric field (1 V.cm −1 ) at 1 kHz. The results revealed an expansion of ferroelectric phase of TGS by 15–55°C with increasing the SiO2 content. Besides, an additional phase transition point which is characteristic for the bulk clusters of TGS was found at low content of SiO2 . The detected anomalies were discussed thoroughly based on the interaction between components in the composite.